P432 Relationship between haemoglobin status and utility in patients with iron deficiency anaemia in inflammatory bowel disease: A post-hoc analysis of a phase, 3 clinical trial. (21st January 2022) - Murphy, D; Wooton, P; Jacob, I
Abstract: Background: Iron deficiency anaemia (IDA) can significantly impair the health-related quality of life of patients with inflammatory bowel disease (IBD), but there is little evidence demonstrating a relationship between haemoglobin (Hb) and utility values. This study aimed to estimate preference-based health state utility values from Short-Form Health Survey (SF-36) data, stratifying by treatment received, and to investigate the relationship between Hb status and health-related quality of life. Methods: A randomised phase, 3b clinical trial compared oral ferric maltol (FM) vs intravenous (IV) iron (ferric carboxymaltose (FCM)) in patients with IBD and IDA who were eligible for IV iron. This post-hoc analysis used patient-level data on SF-36 responses to generate Short-Form Six-Dimension (SF-6D) and EuroQol-5 Dimension (EQ-5D) health-state utility values using published algorithms. Utility values were further stratified by the proportion of patients achieving normalisation of Hb levels (Hb >, 13g/dL for men and >, 12g/dL for women). Results: In the overall study population, mean (SD) SF-6D values were, 0.67 (±0.12) at baseline and, 0.70 (±0.13) at, 52 weeks. Mapped mean EQ-5D values were, 0.77 (±0.17) at baseline and, 0.78 (±0.19) at, 52 weeks. There were no significant differences in the mean utility estimates for patients receiving FM and FCM at any assessment point (Table, 1). Of note, 45.38% of patients randomised to the FCM arm received repeat treatments after the initial course administered at baseline. In the overall study population, mean utility estimates for patients in a normalised state were significantly greater than those estimated for patients in a non-normalised state (pooled analysis of all time points): SF-6D, 0.724 (95% CI:, 0.717–0.731) vs, 0.690 (95% CI:, 0.683–0.697), respectively, Pr (|T|>|t|):, 0.001; EQ-5D, 0.834 (95% CI:, 0.826–0.842) vs, 0.792 (95% CI:, 0.782–0.802), Pr (|T|>|t|):, 0.001. No statistically significant differences were observed between treatments in the normalised or non-normalised groups. Conclusion: Oral ferric maltol results in similar utility scores to IV iron therapy with ferric carboxymaltose in patients with IBD eligible for intravenous iron therapy. Normalised Hb was associated with significantly better utility than non-normalised, demonstrating the value to patients of treating IDA in IBD. A cost-effectiveness analysis should be conducted to examine the incremental benefit of IV iron considering the large cost of treatment.